1991
DOI: 10.2307/1242895
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Economic Efficiency of Producing Rural Road Services

Abstract: The research reported here examines the ability of a sample of Midwest township officials to produce low-volume rural road services in an economically efficient manner. Farrell-type measures of input use and scale efficiency are reported. Results suggest that over 50% of costs may be unnecessarily incurred because of input use inefficiency. Correlation between output measures and the efficiency measures suggests that larger jurisdictions are more efficient than smaller jurisdictions. In addition, 84.5% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Such a framework is not only consistent with the size economies literature (i.e., long-run average cost curves) but also conforms to the Inman (1979) two-step decision making process (Deller and Nelson, 1991). In particular, the first step of the process corresponds to provisionary decisions (demand or public choice) while the second step refers to production related decisions.…”
Section: A Theoretical Frameworksupporting
confidence: 77%
See 2 more Smart Citations
“…Such a framework is not only consistent with the size economies literature (i.e., long-run average cost curves) but also conforms to the Inman (1979) two-step decision making process (Deller and Nelson, 1991). In particular, the first step of the process corresponds to provisionary decisions (demand or public choice) while the second step refers to production related decisions.…”
Section: A Theoretical Frameworksupporting
confidence: 77%
“…There are, however, a small handful of empirical studies which do indicate the presence of managerial inefficiencies in local governments. In a study of rural road services in the Midwest, Deller and Nelson (1991) found that of the 446 townships studied, less than one percent were identified as managerially efficient. A consistent pattern identified by Deller and Nelson confirms the hypothesis concerning the relatively higher levels of inefficiency at the smallest levels of local government.…”
Section: Managerial Efficiency In Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies identify substantial size inefficiencies and conclude that cost reductions could be realised by restructuring the production of rural roads. Deller and Nelson (1991), Deller et al (1992), Deller (1992) and Deller and Halstead (1994), on the other hand, investigate the technical efficiency of rural road maintenance using different parametric and non-parametric estimation techniques. Their estimation results suggest that road maintenance costs are 14 to 50 percent higher than necessary due to production inefficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency index derived from the equation (1.3) can be used as a measure of the performance of farmers. Based on previous studies, the influence of efficiency of farmers by Ordinary Least Square (OLS) has been used by [10] to identify this factor through a regression model. Since the measurement of efficiency is censored with the value between 0 and 1, hence some arguments state that the estimation of OLS is inconsistent and inefficient [11].…”
Section: Tobit's Analysismentioning
confidence: 99%